Exosome-derived circ-001422 promotes tumor-associated macrophage M2 polarization to accelerate the progression of glioma - Wenpeng Cao; Zhirui Zeng; JianFei Sun; Yunhua Chen; FaGuang Kuang; Shipeng Luo; Jinzhi Lan; Shan Lei (Communications Biology)
Abstract Cytokines, tumor cells, and tumor-associated macrophages play crucial roles in the composition of glioma tissue. Studies have demonstrated that certain cytokines can induce M2 polarization of tumor-associated macrophages and contribute to the progression of glioma. Nonetheless, the intricate molecular interactions among cytokines, glioma cells, and tumor-associated macrophages remain largely unexplored. To investigate this cross-talk, a combination of RNA-sequencing, chromatin immunoprecipitation, immunoprecipitation, exosome isolation, and biological experiments were employed. Treatment with IL-6 significantly increased circ-001422 expression in glioma cells. A poorer prognosis was associated with elevated levels of circ-001422 in glioma tissues. Circ-001422 was transcribed directly by STAT3 through binding to its promoter. Circ-001422 exerted cancer-promoting functions when co-cultured with M2 macrophages. Furthermore, glioma cells were found to transfer circ-001422 to macrophages via an exosomal pathway, promoting M2 polarization. Mechanically, circ-001422 interacted with p300, resulting in STAT3 acetylation, thus promoting nuclear localization and transcriptional activity of STAT3/NF-κB and M2 macrophage polarization. In conclusion, glioma cells released exosomes enriched with circ-001422, which in turn induce M2 macrophage polarization by activating the STAT3/NF-κB pathway, thereby enhancing the aggressive characteristics of glioma cells. Targeting circ-001422 may represent a potential therapeutic approach for glioma.